A feast-and-famine pattern of sleep: Do railway staff get the sleep they need?. (July 2022) - Basacik, Dan; Tailor, Anisha
Abstract : The relationship between sleep and health and wellbeing is receiving increasing attention in our society, following decades of research that has demonstrated the impact of insufficient sleep on performance and health. Fatigue has been identified as a factor in 21% of high-risk incidents in the GB rail industry, and insufficient sleep and long periods of being awake are known to be two key contributors to fatigue. This paper presents evidence from a recent survey conducted in the GB rail industry, which enabled the sleep and wakefulness of railway workers to be quantified. There were 7807 responses to the survey, which represents a very large sample. Responses were primarily collected online, though paper copies were made available in some organisations. Respondents reported sleeping less when working nights, more when working days, and the most on days off, which suggests a feast-and-famine pattern of sleep. 41% were getting 6 h of sleep or less when working days, compared to 63% when working nights. Getting 6 h or less of sleep was associated with excessive daytime sleepiness. Although it is accepted that individuals' sleep requirements vary, the patterns that shift workers reported in this survey suggest that many are not achieving the amount of sleep they need. The findings of the survey presented in this paper highlight that there is work to be done to understand and address the causes of insufficient sleep in railway workers.